what is Mathematical Induction, solved problems on Mathematical Induction
Mathematical induction is a mathematical technique to prove statements. mathematical induction involves two steps:
- Basic step: to prove the given statement is true for the initial value. (f(0) is true)
- induction step: to assume statement true for k ( F(k) is true) and then prove it is true for F(k+1) then p(n) is true for natural numbers.
Examples:
- Prove that 5ⁿ - 1 is divisible by 4 for all n>=1
step-1: basic step : true for n=1
F(n)=5ⁿ - 1
F(1)=5¹-1
F(1)= 4
F(n) is true for n=1
step 2: Induction step
first, we will assume the given statement is true for value k i.e.
2. Prove that n³ + 2n is divisible by 3 for all n>=1.
solution:
step-1: basic step : true for n=1
F(n)=n³ + 2n
F(1)=(1)³+2(1)
F(1)=1+2
F(1)=3 which is divisible by 3.
hence the given statement is true for n=1.
step 2: Induction step
first, we will assume the given statement is true for value k i.e.
F(k): k³-2k=3m is true
to prove :
F(k+1): (k+1)³+2(k+1)=3m is true
proof:
RHS=(k+1)³+2(k+1)
RHS=(k³+1+3(k)²(1)+3(k)(1)²)+2(k+1)
RHS=(k³+1+3k²+3k)+2k+2
RHS=(k³+1+3k²+3k)+2k+2
RHS=(k³+2k)+2+1+3k²+3k
RHS=(k³+2k)+3k²+3k+3
RHS=(k³+2k)+3(k²+k+1)
here,
F(K)=(k³+2k) and 3m=3(k²+k+1)
RHS=F(k) + 3m
so it is true for F(k+1)
and hence it is proved n³ + 2n is divisible by 3 for all n>=1.
3. prove this 1+2+3+-------+n = n(n+1)/2
solution:
step-1: basic step : true for n=1
F(n): 1+2+3+-------+n = n(n+1)/2
LHS= 1 for F(1)
RHS= n(n+1)/2=(1+1)/2=1=LHS
so the given statement is proved for F(1)
step 2: Induction step
first, we will assume the given statement is true for value k i.e.
F(k): 1+2+3+-------+k = k(k+1)/2 is true ..... eq 1
To prove:
F(k+1): 1+2+3+-------+(k+1)= k((k+1)+1)/2 is true........eq 2
from eq 1.
1+2+3+-------+k = k(k+1)/2
by adding (k+1) to both sides
1+2+3+-------+k+(k+1) = k(k+1)/2 +(k+1)
1+2+3+-------+k +(k+1)= k(k+1)+2(k+1)/2
1+2+3+-------+k +(k+1)= (k²+k+2k+1)/2
1+2+3+-------+k +(k+1)= (k²+3k+1)/2
k²+3k+1=k²+2k+K+1
(k²+3k+1)=k(k+2)+1(k+1)
(k²+3k+1)=(k+2)(k+1)
1+2+3+-------+k +(k+1)=(k+2)(k+1)/2
hence proved F(k+1) is also true
and hence the given statement is true.
3. Prove this: 1+3+5+------+(2n-1)=n²
Solution:
step-1: basic step : true for n=1
F(n): 1+3+5+------+(2n-1)=n²
LHS=1
RHS=(1)²=1=LHS
hence F(1) is true.
step 2: Induction step
first, we will assume the given statement is true for value k i.e.
F(k):1+3+5+------+(2k-1)=k² .....eq (1) is true.
To prove:
F(k+1):1+3+5+------+(2(k+1)-1)=(k+1)² .... Eq (2)
Proof:
LHS=1+3+5+------+(2(k+1)-1)
LHS=1+3+5+------+(2k+1)
LHS=1+3+5+------+(2k+1)
last second odd term is (2k-1){(2k+1-2) # difference between two consecutive odd term is 2}
LHS=1+3+5+------+(2k-1)+(2k+1)
{1+3+5+------+(2k-1)=F(k)=k²}
LHS=k²+2k+1
LHS=(k+1)²=RHS
hence proved the given statement is true for F(k+1)
and hence the given statement is true for n.
4.prove that n³-n is divisible by 3for any positive integer n.
Solution:
step-1: basic step : true for n=1
F(n): n³-n = 3n
F(1):1-1=0 which is true for F(1)
step 2: Induction step
first, we will assume the given statement is true for value k i.e.
F(k):k³-k=3m is true
To prove:
F(k+1): (k+1)³-(k+1)=3m
Proof :
LHS=(k+1)³-(k+1)
LHS=(k³+1+3k²+3k)-k-1
LHS=k³+3k²+3k-k
(k³-k =3m means it is divisible by 3)
(3k²+3k is also diviblr by 3)
hence it is proved for F(k+1)
and the given statement is true for n.
5. prove that (3ⁿ-1) is a multiple of 2.
solution:
step-1: basic step : true for n=1
F(n):3n-1
F(1)=3-1=2 which is a multiple of 2.
step 2: Induction step
first, we will assume the given statement is true for value k i.e.
F(k): is true
3k−1
3k−1
3k−13k−1 is a multiple of 2 is to prove:
F(k+1) :
3k+1–1 is a multiple of 2
proof:
3k+1−1=3×3k−1=(2×3k)+(3k−1)
so it is proved for F(k+1)
and hence it is true for n also.
Comments
Post a Comment